2014
DOI: 10.1002/mbo3.202
|View full text |Cite
|
Sign up to set email alerts
|

Dietary differences are reflected on the gut prokaryotic community structure of wild and commercially reared sea bream (Sparus aurata)

Abstract: We compared the gut prokaryotic communities in wild, organically-, and conventionally reared sea bream (Sparus aurata) individuals. Gut microbial communities were identified using tag pyrosequencing of the 16S rRNA genes. There were distinct prokaryotic communities in the three different fish nutritional treatments, with the bacteria dominating over the Archaea. Most of the Bacteria belonged to the Proteobacteria, Firmicutes, Actinobacteria, and Bacteroidetes. The number of bacterial operational taxonomic unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
87
0
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(109 citation statements)
references
References 61 publications
16
87
0
6
Order By: Relevance
“…Because of the multitude of different DNA extraction methods and analytical methods for investigating these samples, there is no universal method to evaluate the bacterial diversity of fish guts. However, Proteobacteria, Firmicutes, and Bacteroidetes were identified as the major phyla in the gut microbiota of the koi carp, which is similar to the results obtained for sea bream ( Sparus aurata ) (Kormas, Meziti, Mente, & Frentzos, ). Previous studies also revealed a core microbiome from the intestines of fish dominated by Proteobacteria, Firmicutes, Bacteroidetes, Actinobacteria, and Fusobacteria (Smriga, Sandin, & Azam, ; Sullam et al., ; Ye, Amberg, Chapman, Gaikowski, & Liu, ).…”
Section: Discussionsupporting
confidence: 85%
“…Because of the multitude of different DNA extraction methods and analytical methods for investigating these samples, there is no universal method to evaluate the bacterial diversity of fish guts. However, Proteobacteria, Firmicutes, and Bacteroidetes were identified as the major phyla in the gut microbiota of the koi carp, which is similar to the results obtained for sea bream ( Sparus aurata ) (Kormas, Meziti, Mente, & Frentzos, ). Previous studies also revealed a core microbiome from the intestines of fish dominated by Proteobacteria, Firmicutes, Bacteroidetes, Actinobacteria, and Fusobacteria (Smriga, Sandin, & Azam, ; Sullam et al., ; Ye, Amberg, Chapman, Gaikowski, & Liu, ).…”
Section: Discussionsupporting
confidence: 85%
“…Information on the archaeal communities associated with the fish gut is scarce, but Archaea have been detected in fecal or intestinal samples of European flounder Platichthys flesus (van der Maarel et al, 1998(van der Maarel et al, , 1999, gray mullet (van der Maarel et al, 1998Maarel et al, , 1999, gilthead seabream Sparus aurata (Kormas et al, 2014), and grass carp Ctenopharyngodon idella (Ni et al, 2014;Xia et al, 2014). Although information is not available for archaeal abundance, the archaeal diversity appears considerably lower than that of the bacterial communities in the fish GI tract (Li et al, 2014;Ni et al, 2014).…”
Section: Microbial Compositionmentioning
confidence: 94%
“…This core community consisted of 52 bacterial lineages and was dominated by members of the class Bacilli, followed by members of the Alphaproteobacteria and Gammaproteobacteria. Further, the comparison of the gut microbiomes of wild and reared individuals of the same species display a great deal of similarity and common community components (Roeselers et al, 2011;Kormas et al, 2014;Rodiles, Waines, Saoud and Merrifield, unpublished date).…”
Section: Factors Affecting the Gut Microbiomementioning
confidence: 97%
See 1 more Smart Citation
“…Besides bacteria, yeasts are frequently isolated from fish gut, more especially in freshwater (Gatesoupe, 2007;Raggi et al, 2014). Archaea have been also reported in very few studies (van der Maarel et al, 1998(van der Maarel et al, , 1999Ni et al, 2014;Kormas et al, 2014), but methanogens would need further attention, as methane production was reported in fish intestine (Oremland, 1979). Very little is known about bacteriophages in fish intestine (e.g.…”
Section: Intestinal Microbiome In Fishmentioning
confidence: 99%